Menelusuri Akar Perbedaan Tafsir Tentang Kepemimpinan Non Muslim(Studi Analisis Linguistik QS. Al-Mâidah: 51) - Fuqoha, Fuqoha (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2016)
This study discusses the interpretation for QS. Al-Mâidah: 51. Research using qualitative and analytical literature finds that there are two models of interpretation for that verse. The first model mentions that the meaning of auliyâ is common which can include leadership, close friends and administrators. That is, it is not permissible to appoint non-Believer as leaders. The second model states that the meaning of auliyâ’ is a secret leak that causes non-Muslims to know the weaknesses of Muslims. The meaning in this verse according to the second opinion is specifically for hypocrites only.